Life History, Developmental Biology and Seasonal Abundance of Idioscopus Nitidulus (Walker) (Homoptera : Cicadellidae) - Mohd Nordin, Abdul Razak (1994)
Harumanis mango in Perl is suffered from the outbreak of leaf hoppers, Idioscopus nitidulus Walk. in 1986 and 1987. The laboratory and field experiments were conducted to investigate some aspects of the biology of mango leafhoppers, initidulus Walk. an important pest of mango flowers and shoots in south East Asia. The synchrony of insect population with the phenology of the plant was also studied. The adults were found to survive on mature leaves in the absence of flowers and shoots. However, reproduction occurred during the onset of flowering and young shoot development. The fluctuating patterns in the abundance of hoppers coincided with the availability of flower panicles and developing shoots. The number of hoppers appeared unaffected by the heights and positions of flower panicles in the tree.